Ecological education of the population as an important component of environmental policy (Journal of actual problems of jurisprudence, 2018)
This article analyzes the concept and role of environmental education as an integral environmental policy of the state. Ecological education is also considered as a method of forming ecological consciousness and ecological worldview of the world population.The purpose of this work is to analyze scientific approaches to the concept, role and essence of environmental education of the population. And also the analysis of the role of the ecological consciousness of citizens in the modern world. When writing the work, both general theoretical and specifically scientific methods of cognition were used, namely dialectical, comparative, legal, historical, formally dogmatic (specifically, legal), specific legal and logical. The scientific and practical significance of the study lies in the results and conclusions.The article analyzes the conceptual apparatus and their correlation, as well as identifies the tasks that still face state and human rights organizations.The practical value of the article is the possibility of using the results obtained to improve the current environmental legislation of the Republic of Kazakhstan, as well as in law enforcement activities of authorized bodies in the field of ecology.Key words: ecology, ecological consciousness, ecological world view, ecological enlightenment.